Intimate Partner Violence and Household Decision Making Autonomy : Effects of the Malian Conflict on Women - Ekhator-Mobayode, Uche Eseosa; Kelly, Jocelyn; Rubin, Amalia; Arango, Diana J. (World Bank, Washington, DC, 2021)
Rates of intimate partner violence vary widely across regions. Evidence suggests that some of this variation can be attributed to exposure to armed conflict. This study exploits variation in the timing and location of conflict events related to the war in Mali to examine the effect of conflict on intimate partner violence and some women’s empowerment outcomes. The study used data from the Demographic and Health Survey spatially linked to conflict data from the Armed Conflict Location and Events Database. Wartime conflict increases the prevalence of women’s experiences of intimate partner violence. It also increases women’s household decision making autonomy but decreases women’s ability to decide how their earnings are deployed. The results imply that to be successful, programs to mitigate these adverse effects of conflict on women need to be context specific and rely on data-driven evidence from situations of conflict whenever possible. Policy makers are called to design programs that address harmful gender norms and intimate partner violence at the individual/household and community levels, especially for women residing in areas with high-intensity conflict. Measurement of women’s empowerment should consistently include several domains of women’s lives to gauge progress in voice and agency, financial autonomy, and violence reduction.